Biosensors for simplistic detection of pathogenic bacteria: A review with special focus on field-effect transistors. (April 2022) - Samota, Sharmistha; Rani, Reetu; Chakraverty, Suvankar; Kaushik, Anupama
Abstract: Among various infectious agents, pathogenic bacteria pose severe threat to human health and worldwide economy as it is difficult to treat several serious bacterial infections. Serious outbreaks of bacterial infections are not only limited to hospitals but are prevalent in food, water, soil and air. Conventional techniques like biochemical assays for bacterial identification are not efficient because these are time consuming, require professional personnel and expensive instruments. It is thus imperative to develop simple, accurate, sensitive, prompt and cost-effective methods that make possible early detection of pathogenic bacteria. This review presents an overview of conventional methods along with recent advances in biosensing techniques used for bacterial detection with special emphasis on FET based biosensors. Application of different nanomaterials in fabrication of Bio-FETs for bacterial detection are also discussed. Further, future scope of some new materials viz. oxide perovskites in context to application in BioFETs will be elaborated which offers an economical, facile and point of care device. Graphical abstract: Image 1 Highlights: A comprehensive review of biosensing of bacterial pathogens. The accomplishments and shortcomings of traditional bacterial detection methods are discussed. FET based biosensing platforms for detection of bacteria are discussed. Future prospects of using oxide heterostructures for FET based biosensing of bacterial pathogens.